Sexual and gender minority publication trends in the dermatology literature - Shahwan, Kathryn T.; Nosewicz, Jacob; Trinidad, John; Carr, David R. (Archives of dermatological research, 2022)
In the greater medical literature, publication rates on topics relevant to the lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ) communities have been on the rise. The publication rates in the dermatology literature have not yet been described. We performed an analysis of the dermatology literature from 1980–2020 to characterize LGBTQ-relevant publication rates and themes over time. PubMed, CINAHL, and Embase were searched using terminology related to sexual and gender minorities and dermatology. Articles were included if they were published in a peer-reviewed dermatology journal, used human subjects, and included terminology related to sexual or gender minorities in the title or abstract. Publication year, journal, study design, corresponding author country, and best-fit article theme were recorded. The searches yielded 2,019 articles, with 225 meeting inclusion criteria. LGBTQ-relevant articles increased substantially over time, particularly between 2015 and 2020. Overall, most centered on HIV and other infectious diseases (62.2%), followed by other dermatologic conditions (20.4%), workforce and culturally competent care (12.4%), and gender-affirming procedures (4.9%). Although the number of infectious disease-related articles also increased over time, representation of the other three themes increased substantially, particularly since 2011. Although sexually transmitted diseases remain a common theme in the dermatology literature, the last 10 years have seen an explosion of publications on other topics such as non-infectious dermatoses, gender-affirming procedures, and access to culturally competent care.